Vascular control mechanisms in normal and lipopolysaccharide-treated rats - Jolly, Lisa (2009)
The development of sepsis is associated with complex cardiovascular changes, some of which can be micmked in animals by administration of lipopolysaccharide (LPS). Animal models have identified a number of mediators important in these changes. The work described within this thesis aimed to investigate the role of adrenomedullin (AM) and adenosine in regulating vascular function in vivo in normal and LPS-treated rats. Integrated haemodynamics were assessed in Sprague Dawley rats following implantation of pulsed Doppler flow probes, allowing changes in renal, mesenteric and hindquarters vascular conductance to be measured across time. Adrenomedullin (AM), a hypotensive peptide involved in cardiovascular regulation, is upregulated in sepsis. Intermedin (IMD) is related to AM and shares some of its functions. However, the in vivo integrated responses to IMD have yet to be determined. In normal rats, both peptides caused marked vasodilatations in all regions, with hypotension and tachycardia. IMD was a more potent vasodilator than equimolar AM. Next, mechanisms involved in IMD signalling were investigated and compared to AM. Both AM and IMD-mediated renal and mesenteric vasodilatation were attenuated by AM22-52 and some components of IMD were sensitive to L-NAME, suggesting IMD causes both endothelial-dependent and -independent vasodilatations. No role for KATP channels was found, but there was an enhanced response to AM in the presence ofU37883A ; this was due to inhibition of the renin-angiotensin system as assessed by the angiotensin II receptor antagonist losartan. To assess whether vascular sensitivity to AM and IMD was affected in an LPS model of endotoxaemia, rats were treated with LPS and responses to peptides were assessed at 1.5 h, 6 hand 25 h. Vascular hyporesponsiveness to both AM and IMD occurred at 1.5 h, but had returned by 25 h regardless of the LPS administration protocol. Thus, vascular hyporesponsiveness appears to be a common phenomenon during the early stages of LPS-induced endotoxaemia. The role of adenosine was then examined in the haemodynamic sequelae of sepsis, since evidence suggests that adenosine-mediated vasodilatations help to maintain regional perfusion in animal models. In control rats, endogenous adenosine caused bradycardia and vasodilatation, whereas there was evidence of regional vasoconstriction in LPS-treated rats. In control animals, exogenous adenosine caused hypotension, tachycardia and vasodilatation, but in LPStreated rats, the adenosine-induced renal (at 1.5 h) and hindquarters (at 6 h) vasodilatations were abolished. As enhanced A1 receptor-mediated vasoconstriction could explain the results in LPS-treated rats, responsiveness to an At-receptor agonist (CCPA) or antagonist (DPCPX) was assessed. There was no evidence for enhanced vasoconstrictor responsiveness to CCP A in LPS-treated rats, but DPCPX caused renal vasodilatation, consistent with endogenous adenosine mediating renal vasoconstriction. Finally, the effects of a subdepressor infusion of adenosine on the haemodynamic responses to AM and IMD were assessed, and vice versa, to determine whether any synergism exists between these agents. No synergism was found between adenosine and AM, but there was functional antagonism between adenosine and IMD in the mesenteric vasculature. Collectively, these studies suggest that the development of novel cardiovascular therapies for treatment of sepsis should be designed to take into account the vascular region, and the time elapsed from onset.